Simulation and test of an agricultural unmanned airboat maneuverability model - Liu, Yufei; Noguchi, Noboru; Ali, Roshanianfard Fard (International Journal of Agricultural and Biological Engineering, 2017)
The objective of this research was to determine the Nomoto model maneuverability indices of an agricultural unmanned airboat which was developed to perform autonomous weeding and paddy growth monitoring in a paddy field. A global positioning system compass and an inertial measurement unit were attached on the airboat body to record the position, heading and angular rate. The zig-zag experiments were adopted to obtain the maneuverability indices. The Matlab-based maneuvering simulations were conducted and compared with field experimental data of circular motion test and sinusoidal running test, respectively. The results showed that the trace error was at sub-meter level, which expounds the validity of the obtained maneuvering indices. The proposed Nomoto model maneuverability indices can be used to improve the airboat precise automatic control in paddy field.Keywords: Nomoto model, unmanned airboat, maneuvering simulation, GPS compass, IMUDOI: 10.3965/j.ijabe.20171001.2538Citation: Liu Y F, Noguchi N, Ali R F. Simulation and test of an agricultural unmanned airboat maneuverability model. Int J Agric & Biol Eng, 2017; 10(1): 88–96.